Exploring private financing for biodiversity conservation: stakeholder perspectives and governance in the case of wildflower strips in Germany - Hannah Bücheler; Claudia Bieling; Arndt Feuerbacher (Ecosystems and People)
This study explores the understudied role of privately financed ecosystem service provision in biodiversity conservation, focusing on the example of wildflower strips in Germany. Using qualitative methods, it investigates the diversity of private financing schemes, stakeholder involvement, scheme implementation and farmers motivations to engage in private schemes. The results draw on literature-based stakeholder analysis and expert interviews, including ecologists and practitioners, in three German federal states: Baden-Württemberg, Bavaria and Lower Saxony. Findings include a stakeholder map, the identification of four types of private financing schemes, and the formulation of 17 design criteria covering ecological, economic, and social aspects. These criteria aim to guide providers and sponsors and to emphasise the diverse nature of private wildflower strip financing schemes and their role as crucial links among farmers, the private sector, and society. The study highlights private schemes as viable alternatives to public funding but raises concerns about quality control and coordination with public measures. Combining publicly funded agri-environment schemes with private financing is controversial among stakeholders. Government intervention could formalise the private market, improving control and protection, possibly limiting private sector flexibility and attractiveness due to higher levels of bureaucracy. In any case, transparency in management and financial structures is crucial. Policy recommendations overall include incentivising private sector conservation involvement, offering tax credits for private financing, improving government mechanisms, streamlining coordination of public and private conservation at the landscape level and fostering stakeholder networking. Consequently, this study lays a foundational framework for further exploration into the realm of private financing in biodiversity conservation.